ASSESSING THE IMPACT OF MOBILE HEALTH SERVICE QUALITY BY THE SOCIAL SECURITY ADMINISTERING BODY ON THE SATISFACTION OF NATIONAL HEALTH INSURANCE PARTICIPANTS - Panjaitan, Raya; Hutajulu, Maulina (Jurnal Manajemen dan Bisnis, 2021)
In a digital era marked by burgeoning e-health initiatives, this study explores the pervasive influence of E-service Quality—encompassing Reliability, Efficiency, Fulfillment, Privacy, Responsiveness, and Contact—on the satisfaction of participants in the National Health Insurance (JKN) program. The objective is to quantitatively assess these dimensions' impacts on user satisfaction among Mobile JKN users in Pematangsiantar. Employing a questionnaire as the research instrument, this study scrutinizes the responses of 100 participants using multiple linear regression analysis via SPSS 25. The findings reveal that while Efficiency exerts a significant positive effect on participant satisfaction, Reliability, Fulfillment, and Responsiveness, although positive, are not statistically significant. In contrast, Privacy and Contact do not significantly influence satisfaction. The study underscores the necessity for BPJS Kesehatan to refine the Mobile JKN application's user interface and optimize the mobile app's utility for a seamless user experience, including secure data practices and biometric login features for phone number changes, aligning with national demographic databases. These insights contribute to the strategic enhancement of health insurance services, driving user satisfaction and security in Indonesia's healthcare system.